Which key performance indicators are most effective in evaluating and managing an in vitro fertilization laboratory? - Fabozzi, Gemma; Cimadomo, Danilo; Maggiulli, Roberta; Vaiarelli, Alberto; Ubaldi, Filippo Maria; Rienzi, Laura (Fertility and sterility, 2020)
The laboratory is the heart of an in vitro fertilization (IVF) clinic, and a quality management system is critical for its administration. We review the main structural, process, and outcome key performance indicators (KPIs) to provide laboratory managers with concrete tools aimed at enhancing the quality of their work. Three concepts must be stressed when dealing with KPIs in IVF: [1] always consider the three types of indicators (structural, process, and outcome related), [2] carefully adapt the control chart to either promptly identify issues and adopt corrective measures, or redefine the control limits in a process called “progress building,” [3] consider that achieving a healthy live birth is a multidisciplinary effort that is subject to several confounders, which must be recognized and accounted for in the analyses. In this regard, future KPIs shared among clinicians and embryologists are desirable to enhance the quality of infertility care for IVF patients.